Occupational Health and Safety Risk Assessment Application in Oil Refinery Using Hazard Identification, Risk Assessment and Risk Control (HIRARC) - Sulaiman, Yoga Aulia; Reza Firnanda; Sindy Nindia M.H; Lutfia Agustin; And Ach. Dafid (Tibuana, 2025)
This research aims to evaluate occupational safety and health (OHS) risks in the oil refinery unit of PT XYZ using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. This method involves three main stages: hazard identification, risk assessment, and risk control. The research was conducted descriptively qualitatively through field observations, interviews, and the use of the HIRARC checklist. The identification results show that several work areas, such as the evaporator, separator, and stabilizer, have a Very High risk level due to extreme pressure and temperature, gas leakage, and the potential for explosion and fire. The risk assessment was conducted by considering the likelihood and consequence of each hazard. The risk control strategies analyzed include technical, administrative, and the use of personal protective equipment (PPE). However, most controls are still dominated by administrative approaches, while technical controls such as gas detection systems and shutdown automation have not been implemented optimally. The implementation of HIRARC has proven to be effective in systematically identifying and controlling risks, and contributing to a safer, healthier, and more productive work environment in the oil and gas industry.